2015
DOI: 10.1214/14-aoas789
|View full text |Cite
|
Sign up to set email alerts
|

Reactive point processes: A new approach to predicting power failures in underground electrical systems

Abstract: Reactive point processes (RPP's) are a new statistical model designed for predicting discrete events, incorporating self-exciting, self-regulating, and saturating components.The self-excitement occurs as a result of a past event, which causes a temporary rise in vulnerability to future events. The self-regulation occurs as a result of an external "inspection" which temporarily lowers vulnerability to future events. RPP's can saturate when too many events or inspections occur close together, which ensures that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Our focus with real data experiments is to demonstrate that the models we analyze are sufficiently complex to capture real-world phenomena and enhance prediction performance relative to naive models. Others have successfully used more complex, difficult to analyze models (cf., [39,17]) which are similar in spirit to those analyzed here. Our claim is not that our approach leads to uniformly better empirical performance than previous methods, but rather that our models capture essential elements of all these approaches and hence our theoretical work provides insights into a variety of approaches.…”
Section: Numerical Experimentssupporting
confidence: 82%
“…Our focus with real data experiments is to demonstrate that the models we analyze are sufficiently complex to capture real-world phenomena and enhance prediction performance relative to naive models. Others have successfully used more complex, difficult to analyze models (cf., [39,17]) which are similar in spirit to those analyzed here. Our claim is not that our approach leads to uniformly better empirical performance than previous methods, but rather that our models capture essential elements of all these approaches and hence our theoretical work provides insights into a variety of approaches.…”
Section: Numerical Experimentssupporting
confidence: 82%
“…Whilst we opted to use crime data to demonstrate its utility, the framework can be used to assess predictions in fields such as ecology (Tuia et al 2008), geophysics (Marzocchi et al 2012) and civil engineering (Ertekin et al 2015). Predictive accuracy measures such as hit rate or PAI have a similar meaning and interpretation irrespective of domain and can therefore be applied directly.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction 1.1. Spatio-temporal point processes and hotspot prediction Many physical and sociological processes of interest take the form of events that occur at discrete points in space and time, including crime (Mohler et al 2011), earthquakes (Zhuang et al 2002) and infrastructure failures (Ertekin et al 2015). These are referred to as spatio-temporal point processes (henceforth denoted STPPs).…”
mentioning
confidence: 99%
“…Wang et al (2016) presented a recurrent marked temporal point process (RMT-PP) and demonstrated its effectiveness in predicting the timing of taxi pick-ups. Log Gaussian Cox process (LGCP) has been used to effectively model temporal events, such as wildfires [30] and infrastructure failures [9], in which the logarithm of the intensity is assumed to be drawn from a Gaussian process. The spatio-temporal point process is a more general framework, and considers both spatial and temporal domains.…”
Section: Related Workmentioning
confidence: 99%